THE IMPACT OF THE DIRECTIVE ON CONSUMER ADR ON NATIONAL LAW: CHALLENGES AND OPPORTUNITIES - Bublienė, Danguolė (Teisė, 2015)
The article analyses the core provisions of the Directive on consumer ADR and the particular problematic aspects related to the unclear (or disputable) provisions of the directive or which are important to decide on the improvement of the Lithuanian ADR system. The article analyses such aspects as the possibility to apply ADR system to arbitration or in other words, the possibility to keep the arbitration as the ADR body, the question of possibilities of the mandatory ADR procedure and binding decision according to the provisions of the directive, the regulation of the group action in ADR procedure, the issue of the implementation of the publicity/confidentiality principle in the ADR system. The author comes to conclusion that the transposition of the provisions of the Directive on consumer ADR into national law undoubtedly will influence national law and will determine certain changes of the legal acts regulating national ADR system. However, it is very important to use this opportunity as the measure to improve national ADR system in order to achieve an effective ADR system on which could rely consumers and businesses. Therefore, the core questions (problematical issues) related to ADR system, such as ADR institutional system, the creation of the basis for private ADR system and others should be resolved. The particular issues have been discussed in the present article are very important as well and the decision should be taken will be related not only to the proper implementation of the Directive on consumer ADR (especially due to the reason that the issues discussed in the present article are not unambiguously described in the directive) but to the effectiveness of the national ADR system as well.